Exploring the Innovative Model of Social Practice Education for College Students based on Course Ideological and Political Education - Chen, Renjun (Transactions on Social Science, Education and Humanities Research, 2024)
College students participate in social practice to cultivate their ideals and beliefs. This is not only an effective way to educate college students on socialist core values, but also a good supplement. On this basis, a teaching philosophy of "people-oriented" and "morality based" was proposed, through research on the "Three Represents" and "Five Represents". Based on the demand for talents in the new era and the actual situation of social practice teaching, this paper proposes an optimization approach for the social practice teaching mode of college students based on ideological and political theory courses in universities.